Reducing economic burden through split-shared care model for people living with uncontrolled type 2 diabetes and polypharmacy: a multi-center randomized controlled trial - Zheng Kang Lum; Jia Yeong Tan; Cynthia Sze Mun Wong; Zi Yin Kok; Sing Cheer Kwek; Keith Yu Kei Tsou; Paul John Gallagher; Joyce Yu-Chia Lee (BMC, 2024)
Abstract Background Interprofessional collaborative care such as a split-shared care model involving family physicians and community pharmacists can reduce the economic burden of diabetes management. This study aimed to evaluate the economic outcome of a split-shared care model between family physicians and community pharmacists within a pharmacy chain in managing people with uncontrolled type 2 diabetes and polypharmacy. Method This was a multi-center, parallel arm, open label, randomized controlled trial comparing the direct and indirect economic outcomes of people who received collaborative care involving community pharmacists (intervention) versus those who received usual care without community pharmacist involvement (control). People with uncontrolled type 2 diabetes, defined as HbA1c > 7.0% and taking ≥ 5 chronic medications were included while people with missing baseline economic data (such as consultation costs, medication costs) were excluded. Direct medical costs were extracted from the institution's financial database while indirect costs were calculated from self-reported gross income and productivity loss, using Work Productivity Activity Impairment Global Health questionnaire. Separate generalized linear models with log link function and gamma distribution were used to analyze changes in direct and indirect medical costs. Results A total of 175 patients (intervention = 70, control = 105) completed the trial and were included for analysis. The mean age of the participants was 66.9 (9.2) years, with majority being male and Chinese. The direct medical costs were significantly lower in the intervention than the control group over 6 months (intervention: -US$70.51, control: -US$47.66, p < 0.001). Medication cost was the main driver in both groups. There were no significant changes in productivity loss and indirect costs in both groups. Conclusion Implementation of split-shared visits with frontline community partners may reduce economic burden for patient with uncontrolled type 2 diabetes and polypharmacy. Trial registration Clinicaltrials.gov Reference Number: NCT03531944 (Date of registration: June 6, 2018).